Hitre železniške povezave - naslednji slovenski infrastrukturni projekt stoletja? - Plevnik, Aljaž (Urbani izziv, 2005)
The debate about building a network of high speed railway connections on Slovene territory after full membership in the EU is becoming ever more pending. Following the Italian initiative discussions are mainly focused on the extension of the high speed railway in the 5th transport corridor from Trieste, across Slovenia, eastwards. This route has also been adopted in national strategic physical and transport development documents, although the professional public voiced its doubts about the feasibility of such a network in our territory, as well as suitability of connections in the 5th corridor. With a review of strategic and programme documents concerning development of railway infrastructure in Slovenia and the EU the article gives argumentation for necessary immediate comprehensive assessment of development possibilities of high speed connections in Slovenia and the definition of pertaining national interests.
Keywords: hitre proge; razvojna strategija; Slovenia; Slovenija; železniške proge; železniški promet; železniško omrežje